Public administration, executive power and constitutional confusion - Rohr, John A. (1997)
This article examines the ambiguity in the meaning of executive power in both the text of the U.S. Constitution and in subsequent judicial interpretations. This ambiguity has had a profound impact on the constitutional position of the public administration. In the recent independent counsel case, the U.S. Supreme Court offered a restrictive interpretation of the President's constitutional powers to remove subordinate officers. This new interpretation could lead to increased congressional control over administrative agencies. - Repsroduced
Keywords: Public administration - United States; United States - Presidents; Presidents; Public administration